2018
DOI: 10.1016/j.jqsrt.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Precise predictions of H 2 O line shapes over a wide pressure range using simulations corrected by a single measurement

Abstract: In this work, we show that precise predictions of the shapes of H2O rovibrational lines broadened by N2, over a wide pressure range, can be made using simulations corrected by a single measurement. For that, we use the partially-correlated speed-dependent Keilson-Storer (pcsdKS) model whose parameters are deduced from molecular dynamics simulations and semi-classical calculations. This model takes into account the collision-induced velocitychanges effects, the speed dependences of the collisional line width an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…3.3.4). The resulting line shapes are in excellent agreement with those measured for many transitions of pure H 2 O and H 2 O in N 2 , under various pressure conditions [140][141][142][143]. It was in particular shown, using an empirical correction procedure similar to that applied to the CMDS predictions of CO line-shapes (cf [125] and Sec.…”
Section: 22a the Keilson-storer Model For The Velocity Collision Ksupporting
confidence: 73%
“…3.3.4). The resulting line shapes are in excellent agreement with those measured for many transitions of pure H 2 O and H 2 O in N 2 , under various pressure conditions [140][141][142][143]. It was in particular shown, using an empirical correction procedure similar to that applied to the CMDS predictions of CO line-shapes (cf [125] and Sec.…”
Section: 22a the Keilson-storer Model For The Velocity Collision Ksupporting
confidence: 73%
“…The measured spectra of Ref. [18] of air-broadened 16 O2 lines in the singlet  band [ ] were retained here for validation of the procedure that we have proposed. Measurements were made at room temperature and for various pressures ranging from 6.7 kPa to 100 kPa (Table 1).…”
Section: Experimental Datamentioning
confidence: 99%
“…In [15,16], it was shown that first-principles calculations based on molecular configurations and intermolecular potentials, combined with a limited amount of information obtained from measurements successfully predicts the shapes of CO and H2O ro-vibrational lines. Indeed, these theoretical calculations are based either on classical molecular dynamics simulations (CMDS) [15] or a combination of CMDS and semi-classical methods (see [16] and references therein). It was shown that the non-Voigt effects observed in the measured spectra are well predicted by these first-principles calculations, for various molecular systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations